The role of regional formal institutions and foreign direct investment in innovation in Chinese enterprises. Issue 1 (1st January 2017) - Qu, Yi; Qu, Ting; Wu, Yaoan
Abstract : China features high degrees of income inequality, regional disparity and regional institutional diversity. With disparities in institutional development across regions, Chinese firms tend to have different levels of innovation as the costs, risks, efficiency and incentives of firms in innovation are affected by the regional institutional building. This article investigates the role of regional formal institutions in the innovation process in Chinese enterprises. It suggests that regional formal institutions (reflected by government support), financial institutions, educational institutions and taxation institutions promote innovation in Chinese firms, while they fail to discover such an impact from legal institutions. Also, regional formal institutions positively moderate Foreign Direct Investment (FDI) spillovers on process innovation.